GENE-43. TARGETING GABPb1L INHIBITS IN VIVO GROWTH OF TERT PROMOTER MUTANT GLIOBLASTOMA. (11th November 2019) - Amen, Alexandra; Lew, Rachel; Ren, Shawn; McKinney, Andrew; Mancini, Andrew; Doudna, Jennifer; Fellmann, Christof; Costello, Joseph
Abstract: Understanding cancer cell immortality in primary glioblastoma (GBM) is essential for the development of more informed treatments. Multiple cancer types, including >80% of GBMs, undergo immortalization by reactivating Telomerase Reverse Transcriptase ( TERT ) through acquired mutations in the TERT promoter. TERT, the catalytically active and rate-limiting subunit of telomerase, functions to maintain telomeres, which cap and protect the ends of chromosomes. Our past work has demonstrated that the transcription factor GABP - and specifically its tetramer-forming isoform GABPb1L - binds and activates the mutant TERT promoter. The generation of CRISPR-induced indels in GABPb1L results in a gradual loss of cell viability in TERT promoter mutant but not TERT promoter wild type tumor cells in vitro, but the extent to which GABPb1L function is compromised in this setting is unclear. Thus, the potential for use of GABPb1L as an effective therapeutic target for TERT promoter mutant GBM requires further investigation. Here, we use CRISPR-based strategies to demonstrate that full knockout of GABPb1L is rapidly lethal in TERT promoter mutant cells in vitro, in association with a decrease in both TERT mRNA and telomerase activity. Heterozygous deletion of GABPb1L in the context of TERT promoter mutations leads to slowed growth of orthotopic xenograft tumors in mice, and prolonged survival. Additionally, inducible RNAi-mediated inhibition of GABPb1L in growing tumors is also capable of decreasing tumor burden and increasing survival, further strongly suggesting that targeting GABPb1L in patient tumors could be a viable treatment strategy. Finally, reduced GABPb1L synergizes with temozolomide (TMZ) therapy such that TMZ treatment in the context of low GABPb1L and low TERT leads to a complete ablation of orthotopic GBM xenografts. These results highlight the potential to improve disease outcomes by targeting TERT through inhibition of GABPb1L, particularly in conjunction with TMZ treatment.